Multistakeholder meeting report: Lessons learned from research on mobility outcomes and food & nutrition security in Vietnam’s Mekong Delta - Vaselli, Alessandra; Duong, Thanh Thi; Savelli, Adam; Tuan, Phuong Thi Mai; Truong, May Tuyet; Huynh Thi, Tuyen Thanh (2024)
On December 6, 2024, CIAT (on behalf of the Alliance of Bioversity International and CIAT and the CGIAR Initiatives on Asian Mega-Deltas and Climate Resilience) convened a multi-stakeholder meeting in collaboration with the National Institute of Nutrition of Vietnam (NIN) and Can Tho University. The event focused on Lessons Learned from Research on Mobility Outcomes and Food & Nutrition Security in Vietnam’s Mekong Delta and involved representatives from CIAT and NIN; CDC Bac Lieu, Ca Mau, Can Tho, Soc Trang, Tien Giang provinces; Can Tho University, Can Tho University of Medicine and Pharmacy, Can Tho Statistics Department and Department of Population and Family Planning; and Dong Thap Department of Health (DoH). This multistakeholder meeting builds on the partnership between the CGIAR initiatives on Asian Mega Deltas (AMD) and Climate Resilience and the National Institute of Nutrition of Vietnam (NIN) to advance climate-sensitive programming in Vietnam’s Mekong Delta. Through this partnership, a mobility questionnaire was developed for inclusion in NIN’s National Nutrition Surveillance Survey (NNS). Pilot data collection took place in Bac Lieu province between September and November 2024. Implemented by the Bac Lieu Department of Health’s Center for Disease Control (CDC), data from 402 mobility questionnaires were collected to fill evidence gaps related to the linkages between various mobility outcomes and household food and nutrition security. During the multistakeholder meeting, participants identified challenges and opportunities of the research pilot and discussed key research uptake and upscaling opportunities for policy impact. The mobility questionnaire is expected to inform multi-sectoral national, regional, and provincial policies, including Vietnam’s National Strategy on Nutrition for 2021-2030 and Vision to 2045 and the National Action Plan on Food Systems Transformation in Vietnam towards Transparency, Responsibility, and Sustainability by 2030.